2017
DOI: 10.1038/nprot.2017.039
|View full text |Cite
|
Sign up to set email alerts
|

FISH-Flow, a protocol for the concurrent detection of mRNA and protein in single cells using fluorescence in situ hybridization and flow cytometry

Abstract: We describe a flow-cytometry-based protocol for intracellular mRNA measurements in nonadherent mammalian cells using fluorescence in situ hybridization (FISH) probes. The method, which we call FISH-Flow, allows for high-throughput multiparametric measurements of gene expression, a task that was not feasible with earlier, microscopy-based approaches. The FISH-Flow protocol involves cell fixation, permeabilization and hybridization with a set of fluorescently labeled oligonucleotide probes. In this protocol, sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 81 publications
(65 citation statements)
references
References 22 publications
0
65
0
Order By: Relevance
“…Additionally, imaging of the cells in the microtrap device on different z-planes demonstrated better spatial resolution of the hybridization probes to designate the detection of a genetic abnormality. This feature cannot be achieved in Flow-FISH analysis [29,30]. The microtrap device provided reduced processing time (18 → 3 h) and lower amounts of FISH probes compared to slide-based processing.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, imaging of the cells in the microtrap device on different z-planes demonstrated better spatial resolution of the hybridization probes to designate the detection of a genetic abnormality. This feature cannot be achieved in Flow-FISH analysis [29,30]. The microtrap device provided reduced processing time (18 → 3 h) and lower amounts of FISH probes compared to slide-based processing.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous proof-of-principle study we demonstrated that RNA flow cytometry, which allows for multi-parameter, concurrent analysis of mRNA and protein in the same cell ( 23 25 ), is applicable to the detection of antigen-specific T cell responses to M. tuberculosis antigens ( 26 ). Here, we utilized a semi-automated RNA flow cytometry platform ( 24 ) to determine whether a multi-parametric (mRNA and protein) assay for T cell memory phenotypes and cytokine production identifies differences between LTBI and active TB.…”
Section: Introductionmentioning
confidence: 99%
“…3b). Considering that resolvability of labeled RNA was generally comparable between both FISH and HCR, these results suggest that HCR performs better than FISH for studies that require concurrent resolvability of both RNA and protein [26][27][28] . We found two potential examples of systematic bias in Hill parameters between RNA-based and protein-based measurements.…”
Section: Attribution Of Performance To Measurandmentioning
confidence: 82%